High Prevalence of Hereditary Cancer Syndromes in Adolescents and Young Adults With Colorectal Cancer - Mork, Maureen E. (J Clin Oncol, 2015)
PURPOSE: Established guidelines recommend evaluation for hereditary cancer syndromes in patients younger than 50 years diagnosed with colorectal cancer (CRC). This group has been well described in the literature; however, patients diagnosed as adolescents and young adults are not well represented in CRC studies. Here, we define the clinical profile, including the extent of hereditary cancer syndromes and family history of cancer, in patients diagnosed with CRC at age 35 or younger. PATIENTS AND METHODS: We reviewed patients who underwent genetic counseling at our institution during 5 years (2009 to 2013). Data were collected regarding demographics, clinicopathologic information, tumor and genetic testing, and family history. Patients with an identified hereditary cancer syndrome were compared with those without a syndrome. RESULTS: Of the 193 patients with evaluable data, 35% had an identifiable hereditary cancer syndrome, including 23 with Lynch syndrome, 22 with mutation-negative Lynch syndrome, 16 with familial adenomatous polyposis, two with constitutional mismatch repair deficiency, two with biallelic MUTYH mutations, and one with Li-Fraumeni syndrome. Patients without a hereditary syndrome more frequently presented with metastatic disease, whereas patients with a syndrome were more likely to present at earlier stages and to have a family history of cancer. Nevertheless, a substantial proportion of the hereditary syndromes (19%) were diagnosed in individuals with no family history of the disease. CONCLUSION: We conclude that patients diagnosed with CRC at age 35 years or younger should receive genetic counseling regardless of their family history and phenotype.